Antibiotic use during pregnancy and the risk of preterm birth: a population-based Swedish cohort study. (2nd March 2022) - Nguyen, M H; Fornes, R; Kamau, N; Danielsson, H; Callens, S; Fransson, E; Engstrand, L; Bruyndonckx, R; Brusselaers, N.
Abstract: Objectives: To assess the impact of gestational antibiotics on the risk of preterm birth, since a healthy maternal microbiome may be protective. Methods: Population-based cohort study including all first pregnancies in Sweden (2006–16). The association between gestational and recent pre-conception systemic antibiotics and preterm birth was assessed by multivariable logistic regression presented as ORs and 95% CIs, adjusted for comorbidities (hypo- and hyperthyroidism, hypertension, or diabetes mellitus pre-gestation), trimester, antibiotic class and treatment duration. Results: Compared with non-users, antibiotic exposure was associated with increased risks of preterm birth in mothers with comorbidities (OR = 1.32, 95% CI 1.18–1.48) and without (OR = 1.09, 95% CI 1.06–1.13). Pre-conception use showed no association, while risk was increased for first and second trimester use and decreased for third trimester use. The increased risks were seen for the following antibiotic groups in mothers without and with comorbidities, respectively: macrolides, lincosamides and streptogramins (OR = 1.63, 95% CI 1.45–1.83; OR = 2.48, 95% CI 1.72–3.56); quinolones (OR = 1.60, 95% CI 1.32–1.94; OR = 2.11, 95% CI 1.12–4.03); non-penicillin β-lactams (OR = 1.15, 95% CI 1.07–1.24; OR = 1.39, 95% CI 1.07–1.83); other antibacterials (OR = 1.09, 95% CI 1.03–1.14; 1.38, 95% CI 1.16–1.63); and penicillins (OR = 1.04, 95% CI 1.01–1.08; 1.23, 95% CI 1.09–1.40). Antibiotic indications were not available, which could also affect preterm birth. Conclusions: Antibiotic use during pregnancy was associated with an increased risk of preterm birth, especially in mothers with chronic diseases.